Development of Android-Based Interactive Learning Media on the Application of Electronic Systems in Automotive Technology - Susilo, Budhi; Wijanarko, Dwi; Sutopo, Yeri (Universitas Negeri Semarang, 2023)
Student understanding of the material is still relatively low, one of the causes being the impractical use of learning media that leverages information and communication technology. One utilization of information and communication technology is the development of Android-based interactive learning media on the application of electronic systems in automotive technology, a core subject in the automotive engineering expertise program at vocational high schools. This research aims to improve the understanding of students regarding the subject matter. The research method uses R&D (research and development) with the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used are: (1) The product, which is an Android-based interactive learning media application called SAC, focusing on the application of electronic systems in automotive technology; (2) The product is deemed suitable based on the Content Validity Index (CVI) score from media experts, which is 0.92, and the Percentage of Agreement (PA) of 96%, while the CVI score from material experts is 0.96 and PA 98%; (3) The product trial results show a high level of effectiveness based on the Independent Sample t Test for N-gain Score with a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference in effectiveness between the experimental and control groups; and (4) The reproducibility coefficient (Kr) and scalability coefficient (Ks) test results are 95% and 90%, respectively, indicating that the Android-based interactive learning media on the application of electronic systems in automotive technology is very practical.